Application of Hybrid Contracts Concept in Islamic Credit Card Products and Murabahah Financing - Syaukani, Syaukani Rahmat; Herdiana, Nana; Yoyok, Yoyok Prasetyo (Yayasan Mentari Madani, 2024)
Contracts are a fundamental element in modern contract and business law. A contract is usually a written agreement between two or more parties that stipulates the rights, obligations and responsibilities of each party regarding a particular transaction or agreement. However, in the ever-evolving business world, there are situations where the needs and objectives of the parties cannot always be accommodated by traditional contract models. Including innovation and business development in the Sharia Card concept and Murabahah bil Wakalah financing are examples of Hybrid Contracts. This research uses a descriptive qualitative methodology to describe and analyze in depth based on the data obtained. The view of fiqh experts regarding hybrid contracts is an important issue in the context of Sharia business. The majority of ulama tend to view hybrid contracts as permissible in Sharia principles, referring to the rule of al-istishab al-ashliyah, which states that everything is considered halal as long as there are no arguments indicating its haraam. However, debate has arisen regarding the hadith which prohibits two buying and selling in one contract. Although there are different views among schools of fiqh, the hybrid contract concept is considered to be applicable in Sharia economic transactions by paying attention to the underlying principles of Islamic law, including the application of the contract concept used in Sharia Cards and murabah bil wakalah contract financing.